Desenvolvimento de produto gastronômico hipossódico como alternativa na dieta de pacientes hipertensos - Ferreira, Daniela de Souza (Universidade do Vale do Rio dos Sinos, 2013)
Introduction: Hypertension has a high prevalence in our country and it is considered one of the major modifiable risk factors for cardiovascular disease. One of the main challenges in accomplishing the non-pharmacological treatment of hypertension, especially in the hospital setting, is the adequacy of dietary sodium intake, since it is known for enhancing flavors and making food more palatable. Objective: To develop two low-sodium high palatability sauces to be offered along the main meals for hospitalized patients with high blood pressure. Results: Satisfactory sensorial results were obtained. Both sauces turned meals more visually attractive, enhanced flavor, smell and texture. Conclusions: There is a real possibility to enhance palatability of low-sodium diets, therefore increasing accomplishment to dietary treatment.
Keywords: Hipertensão arterial sistêmica; Dieta hipossódica; Gastronomia hospitalar; Hypertension; Low-sodium diet; Gastronomy applied to hospital food